The "hunting effect" in the cathode region of a vacuum arc; Proceedings of the 20th International Symposium on Discharges and Electrical Insulation in Vacuum, Tours, july 1-5, 2002 - Mesyats G. A. Gennady Andreyevich (2002, 2002)
В фонде НТБ ТПУ отсутствует